Foyle's war. Eagle day Set 1, part 4 [videorecording (DVD)] - Silberston, Jeremy; Kitchen, Michael; Howell, Anthony, 1971-; Weeks, Honeysuckle, 1979-; Ovenden, Julian (Acorn Media, 2003)
While investigating a murder, Foyle uncovers a plot to steal art treasures being moved from the local museum to Wales for safekeeping.